(untitled) (Heritage, 2020)
The portrait of grand knez Vukan, the only modern and fragmentarily preserved one, was located on the north wall of the tower of the main entrance to the Studenica monastery. It is assumed that there was a composition on the north wall of the main entrance in which Simeon with his three sons approaches the Mother of God and Christ. There is a possibility that Vukan, as one of the ktetors of Studenica, was shown in the ktetor’s composition. Since then, Vukan has been shown only with Stefan in compositions that illustrate scenes from the Life of Saint Simeon, in Radoslav’s narthex and monasteries Gradac and Sopoćani. Due to the usurpation of Stefan`s supremacy, Vukan became a sinner who broke his father’s vow to live in harmony with his brother. However, after the end of the civil war, the brothers reconciled: Vukan repented for everything that he had done, and Stefan forgave him everything. The peace between them was established by Sava’s arrival with the relics of Saint Simeon. Saint Sava arranged the reconciliation of the brothers, and he laid the ideal of brotherly love and harmony in the basis of the ruling ideology of Nemanjić`s dynasty. He wanted to emphasize this through paintings, fitting the portraits of his brothers into the iconographic program of the frescoes of the Studenica monastery, and he introduced their names in the founder’s inscription. After the frescoes created in 1208/9. Vukan was painted where it made sense, as someone who, in agreement with his brother Stefan, transfers theirs father’s relics. Since he does not belong to the main lineage of the dynasty, his portrait wasn`t painted in the family compositions of Nemanjićs in the 13th century.